Analisis Perbandingan Kinerja Keuangan Bank Rakyat Indonesia (BRI) dan Bank Negara Indonesia (BNI) - Suginam Suginam; Maringan Sianturi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Financial performance can be described from the work that has been charged to the executor of the task. Financial performance as an illustration of the achievement of the company's success which can be interpreted as the results obtained from various activities carried out. In assessing financial performance, ratio analysis is needed where this ratio analysis can clearly describe the financial condition of a company. Analysis of the financial statements in the form of these ratios, among others, the first is the liquidity ratio, this ratio shows aspects of the company's ability to meet obligations that are due in the short term. CAR, ROA and LDR are aspects that can be used to measure the performance of the company. This research was conducted using a comparative approach, a comparative research approach is a comparative research, which is conducted to compare the similarities and differences of 2 or more properties and facts of the object under study based on a certain framework of thought. The type of data in this study is quantitative data in the form of financial statement figures at Bank BRI and Bank BNI. The technical analysis of the data used in this research is by using comparative analysis, which is a technique using the average test or different tests with unequal treatment. From the results of research that has been carried out to see the financial performance of BRI Bank and BNI Bank, there is no difference in the financial performance of the two banks. By conducting a Differential Test on the value of CAR, ROA and LDR, it can be used as a benchmark to measure the financial performance of the two banks.